POLARISASI TAHAPAN KEPEMIMPINAN TRANSFORMATIF PENDIDIKAN ISLAM - Syadzili, Muhamad Fatih Rusydi (JURNAL AL-TANZIM, 2019)
The purpose of writing this article is to find out the polarization of the stages of leadership that are appropriate to be applied in educational institutions. The current problem of Indonesian education is that the quality is not optimal and evenly distributed. The method and type of data collection in this study is library research by collecting books, journals and the results of previous studies that support the research theme, including literature on leadership which includes transformational, Islamic Education and objective leadership models. The results of this study show that the leadership variables are the most important and urgent variables in an effort to create / realize quality education.